2011
DOI: 10.1007/s12275-011-1127-9
|View full text |Cite
|
Sign up to set email alerts
|

Cupriavidus and Burkholderia species associated with agricultural plants that grow in alkaline soils

Abstract: The presence of Burkholderia, Cupriavidus, and Ralstonia species in northeastern Mexico was investigated. An analysis of the root surrounding soil from different agricultural plants led to the isolation of Burkholderia and Cupriavidus species but no Ralstonia strains. Most Cupriavidus species were unknown and grouped into two clusters according to ARDRA profiles. The 16S rRNA sequence analysis showed that the Cupriavidus isolates were highly related among them and with different Cupriavidus species with valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…All Burkholderia strains that were tested on minimal medium showed tolerance to acid pH (pH 4.5). Similar results were obtained by Estrada‐de los Santos and colleagues (), who reported that most of the 43 tested Burkholderia species were able to grow in a pH range of 5–11, although the medium used in their study was neither buffered nor was growth quantitated. Our results are in agreement with previous reports (Belova et al ., ; Aizawa et al ., 2010; 2011; Schmerk et al ., ) and suggest that Burkholderia are acidotolerant rather than acidophilic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All Burkholderia strains that were tested on minimal medium showed tolerance to acid pH (pH 4.5). Similar results were obtained by Estrada‐de los Santos and colleagues (), who reported that most of the 43 tested Burkholderia species were able to grow in a pH range of 5–11, although the medium used in their study was neither buffered nor was growth quantitated. Our results are in agreement with previous reports (Belova et al ., ; Aizawa et al ., 2010; 2011; Schmerk et al ., ) and suggest that Burkholderia are acidotolerant rather than acidophilic.…”
Section: Discussionsupporting
confidence: 88%
“…Burkholderia species have also been isolated from acidic Sphagnum peat bogs (Belova et al ., ; Opelt et al ., 2007a; 2007b), from root tissues of the highly acidifying cluster rooted Lupinus albus (Weisskopf et al ., ) or from soils as acidic as pH 2.9 (Curtis et al ., ). To the best of our knowledge, only one study reported isolation of Burkholderia strains from an alkaline environment (Estrada‐de los Santos et al ., ). While the pH of the rhizosphere soil investigated in this study was high (8.7), the isolated strains were all able to grow at low pH (4.5).…”
Section: Introductionmentioning
confidence: 97%
“…Four Cupriavidus strains were isolated from the Agave L. rhizosphere in San Carlos county in Tamaulipas state, Mexico [6]. Tamaulipas state is located in the northeast of Mexico, and the town of San Carlos is situated at the approximate geographic coordinates N 24° 34′ 40.8, W 98° 56′ 38.36″.…”
Section: Isolation and Ecologymentioning
confidence: 99%
“…As the species have been isolated from many different types of environments all over the world, we expect that many more will be discovered. During an analysis of the distribution of Burkholderia sensu lato in northeast Mexico, we isolated several bacteria from alkaline rhizospheric soils that later were identified as Cupriavidus species [6]. Among them, the novel species Cupriavidus alkaliphilus and Cupriavidus plantarum were described [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the physiology and potential weathering activity of these bacterial communities has still not been adequately addressed and represents a knowledge gap in understanding the diversity involved in silicate weathering. Although vegetation plays a key role in structuring bacterial diversity (Estrada-de los Santos et al 2011, Hartmann, Schmid et al 2009, Miniaci et al 2007, at the critical-zone, secondary regulation may also be occuring due to the action of temperature regime and weathering rates themselves.…”
mentioning
confidence: 99%